A POPULATION-BASED STUDY ON THE DEMOGRAPHIC AND CLINICAL PARAMETERS AMONG CHILDHOOD LEUKEMIA SURVIVAL - Ali, Nabihah; Saupin, Saihpudin; Bahtiar, Balqis; Shamsudin, Shamsul Bahari (Universitas Airlangga, 2024)
Introduction: Leukemia is the commonest childhood cancer among children aged 0-19 years in Malaysia, constituting approximately 39.1% of all pediatric cancer cases in the country. Aims: This study aimed to measure the characteristics and survival of childhood leukemia among the local Malaysian population. Methods: This was a retrospective cohort study based on all the childhood leukemia patients aged 0-19 years registered in the Malaysian National Cancer Registry between 2010 and 2014 with the date of death before or on the 31st December 2019. The Kaplan-Meier method and life table were used to estimate five-year survival rates. Statistical analysis was performed using SPSS (version 27). Result: A total of 1,212 participants were included in this study. Their mean (SD) age was 8 (5.6) at the time of diagnosis. The highest five-year survival estimates were seen in females (58%, 95% CI: 54.5-63.1), children aged 1 to 4 (66%, 95% CI: 62.3-70.9), Indian (61.6%, 95% CI: 50.2-73.0), children diagnosed with acute lymphoid leukemia (ALL) (65.7%, 95% CI: 61.6-69.8), and those who had undergone chemotherapy at diagnosis (57.3%, 95% CI: 54.0-60.6). Patients with childhood leukemia in Malaysia reported a 5-year overall survival of 56.4 %. Survival was greater in children aged 1 to 4 years old, Indians, with ALL, and have had chemotherapy treatment at the time of diagnosis. Conclusion: The study demographic and clinical findings were comparable with other Asian countries.